Composition and Biological Activity of Fetoplacental Tissues-Derived Cryoextracts Being Differently Obtained - Repin, Mykola; Chizh, Yuliia; Marchenko, Larysa; Govorukha, Tetyana; Narozhnyy, Stanislav (Problems of Cryobiology and Cryomedicine, 2023)
The protein-peptide composition of fetal tissues (FTCEs) and placenta (PCE) cryoextracts of rats was investigated by gel permeation chromatography. Cryoextracts were derived from tissue homogenates using the freeze-warming modes: 1 – single (–20°С); 2 – double (–20; –196°С) and 3 – triple (–20; –196; –196°С) ones. The biological activity of cryoextracts was in vitro evaluated by the phagocytic activity of neutrophil granulocytes (NG) of the blood of intact rats after incubation with an inactivated culture of Staphylococcus aureus (2 × 109 cells/ml) for 45 and 120 min for the concentrations of extracts in the incubation medium: 1.6; 3.1; 6 mg/ml in terms of dry substance. The use of mode 3 ensured a greater yield of total protein and low molecular weight compounds of a protein-peptide nature in the composition of cryoextracts. The content of low-molecular-weight fractions in FTCE exceeded that in PCE, regardless of the obtaining mode. Incubation of NG with cryoextracts did not signifi cantly increase the number of neutrophils which entered into phagocytosis. However, all the samples of PCE and FTCE were characterized by a dose-dependent rise in the NG absorption activity during the 45-minute incubation compared to the control. Probl Cryobiol Cryomed 2023; 33(1):003–013